A violência de gênero na pandemia: uma análise na rede social Twitter - Barbosa, Ana Paula Silva (Brasil, 2022)
Gender violence encompasses a much broader concept than premeditated violence, and it is present in the lives of women in situations of violence such as children and adolescents, women and the elderly. And, for that, we will analyze the new forms of violence used in modern society against women, which leaves the palpable reality of multiple violence, and moves to a new social space, the virtual one. Therefore, this study has the purpose of presenting as a general objective to carry out an analysis on the growth of gender violence in the pandemic caused by covid-19, year 2020, and as specific objectives, to investigate the violence expressed in posts on the social network. Twitter and map the forms of violence against women suffered on the social network Twitter, in the year 2020. For this, it appropriated bibliographic methodologies and digital ethnography or Netnography, favoring quantitative and qualitative analyses. Therefore, the research revealed that despite the conquest of several spaces of female empowerment in the networks, violence is still present in their feeds, affecting virtual and real life, causing several drastic consequences for women, consequences arising from the propagated gender inequality. by society.